NPM-ALK-reactive T-cell responses in children and adolescents with NPM-ALK positive anaplastic large cell lymphoma. (2nd September 2019) - Singh, Vijay Kumar; Werner, Sebastian; Schwalm, Simone; Lennerz, Volker; Ruf, Stephanie; Stadler, Serena; Hackstein, Holger; Reiter, Alfred; Wölfel, Thomas; Damm-Welk, Christine; Woessmann, Wilhelm
ABSTRACT: The oncoantigen nucleophosmin-anaplastic lymphoma kinase (NPM-ALK) induces cellular and humoral immune responses in patients with NPM-ALK-positive anaplastic large cell lymphoma (ALCL). We characterize the NPM-ALK-specific T-cell responses in a cohort of pediatric and adolescent ALCL-patients in remission without Human Leucocyte Antigen (HLA)-preselection. First, we assessed NPM-ALK-reactive T-cell responses and their HLA-class I restriction in patients by using dendritic cells (DCs) transfected with in vitro transcribed (IVT) NPM-ALK-RNA for CD8 (n = 20) or CD3 (n = 9) T-cell stimulation. NPM-ALK-specific T-cells were detected in twelve of 29 patients (nine of 20 with CD8-selected and three of nine with CD3-selected cells). Recognition of NPM-ALK was restricted by HLA-C alleles in six of eight, and by HLA-B alleles in four of eight analyzed patients. No NPM-ALK-reactivity was detected in 20 healthy individuals. Second, in order to define possible immunogenic NPM-ALK-epitope regions, DCs pulsed with pools of overlapping long NPM-ALK-peptides were used to stimulate T-cells in further 22 patients and ten controls. Responsive T-cells were detected in 15 patients and in five controls. A peptide pool located in the middle of the kinase domain induced ALK-reactive T-cells in 14 of 15 responsive patients. We could narrow to single peptides between p327-p370 of NPM-ALK in four patients. In conclusion, using IVT-RNA, 40% of NPM-ALK-positive ALCL-patients in remission had detectable NPM-ALK-specific T-cell responses which were mainly restricted by HLA-B and -C alleles. Peptide stimulation of T-cells revealed responses in almost 70% of patients and allowed describing an immunogenic region located in the ALK-kinase domain.